Surface modified cross-linking agent and method for controlling particle size of polymer water-absorbing resin

By using specific surface modification crosslinking agents on polymer water-absorbing resins, combined with spray mixing and heat treatment technology, the resin particle size distribution was successfully controlled, the problem of large particles and micropowders was solved, the liquid-through performance of the resin was improved and the stability of physical properties was maintained.

CN116410489BActive Publication Date: 2025-04-01YIXING DANSON TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111664892.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-04-01
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to suppress the generation of coarse particles above 600 μm while ensuring that the properties of polymer water-absorbing resins do not decrease, and at the same time avoid the increase of fine powders less than 150 μm.

Method used

A surface modification crosslinking agent of a polymer water-absorbing resin is used, including hydrophilic polyols above C3, ether compounds containing covalent bonds reacted with carboxyl groups and liquid silicon, and mixed with SAP base resin in a spray form, and heat treatment is carried out under an environment of 125-140°C to control particle size distribution.

Benefits of technology

The modified SAP resin particle size was effectively controlled, so that the proportion of particles with particle size less than 600μm reached more than 65%, and the proportion of particles with particle size greater than 850μm was less than 4%. At the same time, the liquid-through performance was improved and other physical properties were maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003451547060000061
    Figure BDA0003451547060000061
  • Figure BDA0003451547060000071
    Figure BDA0003451547060000071
  • Figure BDA0003451547060000072
    Figure BDA0003451547060000072
Patent Text Reader

Abstract

The invention relates to a surface modified cross-linking agent and method for controlling the particle size of a polymer water-absorbing resin, characterized in that the surface modified cross-linking agent comprises the following raw materials in 100% by weight: 20-30% of a hydrophilic polyol above C3, 1-5% of an ether compound containing a covalent bond formed by reacting with a carboxyl group, 5-25% of liquid silicon, and the balance being water; the liquid silicon is an aqueous suspension containing amorphous and active silicon dioxide particles with a mass concentration of 20-50%; after preparation, the liquid silicon is uniformly mixed with an SAP base resin in the form of a spray, and heat-treated for 30-60 minutes under an environment of 125-140° C., so as to obtain a surface-modified SAP resin, wherein after the surface modification, particles with a particle size of less than 600 μm account for more than 65%, particles with a particle size of greater than 850 μm account for less than 4%, and the liquid permeability of the modified SAP is greatly improved, and other physical properties such as centrifugal water retention rate and pressurized absorption rate are not reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a surface modified crosslinking agent and a method for controlling the particle size of a polymer water-absorbing resin. Background Art

[0002] SAP is a new type of functional polymer material with a three-dimensional network structure. It has a strong water retention capacity and the water absorbed by it is difficult to overflow under certain pressure conditions. SAP is divided into three categories based on its raw materials: starch, cellulose and synthetic resin, as well as organic-inorganic composite. Among them, the raw materials for synthesizing SAP are mainly polyacrylate series and modified polyvinyl alcohol series.

[0003] Granular SAP varies according to its use. Granular SAP used in sanitary products mainly uses granular SAP with a particle size of 150μm or more and less than 850μm. Micropowders smaller than 150μm will reduce the liquid permeability of the water-absorbing resin, and will fly in the form of dust when processed into sanitary products, causing a deterioration in the operating environment; while particles larger than 850μm are usually irregular in shape. When used as sanitary product materials, the most obvious thing is that the liquid absorption speed is greatly reduced, and the experience of skin contact is very unfriendly.

[0004] The particle size of SAP base resin tends to increase after surface cross-linking treatment, and the number of particles larger than 600μm increases. This is because after the SAP base resin is mixed with the surface cross-linking agent solution, it aggregates after heating and is difficult to disperse without external intervention. The increase of large SAP particles will increase the load of the pulverizer and increase production costs. In addition, the increase of large SAP particles will cause the water absorbent to absorb liquid more slowly, the amount of liquid absorption and re-infiltration to increase, and the dryness to deteriorate.

[0005] The prior art has proposed many methods for controlling the particle size of granular SAP in various processes, including polymerization process, hydrogel polymer fine particle process, dried product crushing, screening and classification process, cooling process after surface cross-linking and post-treatment process, etc. Some of these methods have excessively high costs, some have low production efficiency, and some significantly deteriorate the physical properties of SAP.

[0006] Therefore, the technical problem to be solved by the present invention is how to perform surface modification on the basis of ensuring the physical properties of SAP so as to suppress the generation of coarse particles larger than 600 μm and not increase or reduce the generation of fine powder smaller than 150 μm. Summary of the invention

[0007] In order to solve the above technical problems, a surface modified crosslinking agent and method for controlling the particle size of a polymer water-absorbing resin are provided. The present invention effectively controls the SAP particle size distribution by surface modifying the SAP base resin and ensures that the physical properties of the modified SAP are not reduced or are increased.

[0008] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0009] A surface modified crosslinking agent with controlled particle size of a polymer water-absorbing resin comprises the following raw materials in 100% by weight: 20-30% of hydrophilic polyols above C3, 3-5% of ether compounds that react with carboxyl groups to form covalent bonds, 5-25% of liquid silicon, and the balance is water.

[0010] Preferably, the raw materials are included in the following weight proportions: 25-28% of polyols above C3, 3-5% of ether compounds that react with carboxyl groups to form covalent bonds, 5-10% of liquid silicon, and the balance is water; more preferably, the liquid silicon accounts for 5-6%.

[0011] Furthermore, the liquid silicon is a dispersion containing 20-50% by mass concentration of nano-silicon dioxide, wherein the particle size of the nano-silicon dioxide is less than 50 nm and the specific surface area is at least 20 m 2 / g; the nano-silicon dioxide is a surface-unmodified nano-SiO2, or the nano-silicon dioxide is a cation- or anion-modified nano-SiO2. The liquid silicon with a mass concentration of 30-40% is preferred, and the nano-silicon dioxide is preferably an amino-modified nano-SiO2.

[0012] Furthermore, the hydrophilic polyol with C3 or above is one or more of propylene glycol, glycerol, butylene glycol, and butanetriol; the ether compound containing the compound that reacts with the carboxyl group to form a covalent bond is one or more of ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, diepoxyglyceryl ether, glycerol tri(1,2-epoxy)propyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, pentaerythritol glycidyl ether, dipropylene glycol diglycidyl ether, trimethylolethane triglycidyl ether, and trimethylolpropane triglycidyl ether.

[0013] Preferably, the hydrophilic polyol with a carbon number of 3 or above is propylene glycol; and the ether compound that reacts with a carboxyl group to form a covalent bond is ethylene glycol diglycidyl ether.

[0014] A particle size-controlled surface modification method for a polymer water-absorbing resin comprises the following steps: preparing the surface modification crosslinking agent, uniformly mixing the crosslinking agent with a SAP base resin in the form of a spray, and performing a heat treatment at 125-140° C. for 30-60 min to obtain a surface-modified SAP resin, wherein after the surface modification, particles with a particle size of less than 600 μm account for more than 65% and particles with a particle size of more than 850 μm account for less than 4%.

[0015] Furthermore, the amount of the surface modification cross-linking agent is 1-5% by weight of the SAP base resin, preferably 5%.

[0016] Furthermore, the heat treatment temperature is preferably 130° C. and the time is 40 min.

[0017] Beneficial technical effects:

[0018] The methods for controlling the particle size of water-absorbent resin particles in the prior art do not involve the influence of the surface cross-linking process of the graded granular water-absorbent base resin on the particle size distribution. The surface modified cross-linking agent formula of the present invention can not only greatly improve the liquid permeability of the modified SAP, but also maintain other physical properties such as centrifugal water retention rate and pressurized absorption rate without reduction, but also reduce the proportion of large particles (particle size greater than 850 μm) and medium particles (particle size between 600 and 850 μm) after surface modification, which greatly ensures that the particle size of the modified SAP resin particles does not increase. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0021] The experimental methods in the following examples without specifying specific conditions are usually measured according to national standards; if there is no corresponding national standard, it is carried out according to the general international standards or the standard requirements proposed by relevant enterprises. Unless otherwise specified, all parts are by weight and all percentages are by weight.

[0022] Where the abbreviation EGDE appears below, it stands for ethylene glycol diglycidyl ether, PG stands for 1,2-propylene glycol, fumed silica stands for fumed silica, and LDH stands for hydrotalcite.

[0023] Example 1

[0024] Preparation of polyacrylic acid-based SAP base resin: 4.16 g of polyethylene glycol diacrylate was dissolved in 4088 g of acrylic acid aqueous solution (monomer concentration 26 wt%) to prepare a monomer aqueous solution, and the solution was degassed under a nitrogen atmosphere for 30 minutes. Then, nitrogen was blown into the reactor while the monomer aqueous solution was maintained at 10° C. to control the dissolved oxygen in the system to be below 1 ppm for nitrogen replacement; 20.8 g of a 10 wt % sodium persulfate aqueous solution and 1.65 g of a 5 wt % L-ascorbic acid aqueous solution were added to the above solution, and polymerization began about 1 minute after rapid stirring;

[0025] The aqueous gel-like cross-linked polymer generated by the polymerization is pre-crushed into 4cm×4cm blocks, and the block-like gel-like cross-linked polymer is conveyed to a granulator for crushing. While crushing, 536g of sodium bicarbonate is added for neutralization (molar neutralization rate 70%). The particles obtained after crushing and neutralization are spread on a metal mesh and dried in a hot air dryer at 140°C for 40 minutes, and then crushed by a grinder. Finally, a sieving machine is used to sieve out SAP base resin particles with a particle size of 150-850μm.

[0026] The obtained SAP base resin particles were subjected to performance tests, and the free swelling capacity (FSC) in physiological saline was measured to be 66.7 g / g, and the centrifugal liquid retention capacity (CRC) was measured to be 43.3 g / g.

[0027] Example 2

[0028] A surface modified crosslinking agent for controlling the particle size of a polymer water-absorbing resin comprises the following raw materials in parts by weight: 27.3 parts of propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 5.9 parts of liquid silicon with a concentration of 30wt%, and 64.7 parts of water; wherein the liquid silicon used is an amino-modified nano-SiO2 dispersion, which is an aqueous dispersion, wherein the particle size of the nano-SiO2 is less than 50nm and the specific surface area is at least 20m 2 / g;

[0029] The surface modified cross-linking agent of this embodiment is obtained by uniformly mixing the raw materials according to the above ratio.

[0030] The particle size control surface modification method of a polymer water-absorbing resin comprises the following steps: 5 g of the surface modification cross-linking agent of the present embodiment is evenly mixed with 100 g of the SAP base resin in the form of atomization, and heat-treated for 40 min in an environment of 130° C., and the time below 130° C. is controlled to be no more than 10 min during the 40 min of heat treatment, and the heat treatment process, i.e., the purpose of controlling the particle size in the surface modification process, is achieved. After the heat treatment is completed, the surface-modified SAP resin is obtained, and the surface-modified SAP resin is subjected to particle size analysis by screening and the particle size distribution is calculated. The particle size data is shown in Table 2, and the physical property data of the surface-modified SAP resin are shown in Table 3.

[0031] Example 3

[0032] A surface modified crosslinking agent for controlling the particle size of a polymer water-absorbing resin comprises the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 5.3 parts of liquid silicon with a concentration of 40wt%, and 65.8 parts of water; wherein the liquid silicon used is an amino-modified nano-SiO2 dispersion liquid, which is an aqueous dispersion liquid, wherein the particle size of the nano-SiO2 is less than 50nm and the specific surface area is at least 20m 2 / g;

[0033] The surface modified cross-linking agent of this embodiment is obtained by uniformly mixing the raw materials according to the above ratio.

[0034] The particle size control surface modification method of a polymer water-absorbing resin comprises the following steps: 5 g of the surface modification cross-linking agent of the present embodiment is evenly mixed with 100 g of the SAP base resin in the form of atomization, and heat-treated for 40 min in an environment of 130° C., and the time below 130° C. is controlled to be no more than 10 min during the 40 min of heat treatment, and the heat treatment process, i.e., the purpose of controlling the particle size in the surface modification process, is achieved. After the heat treatment is completed, the surface-modified SAP resin is obtained, and the surface-modified SAP resin is subjected to particle size analysis by screening and the particle size distribution is calculated. The particle size data is shown in Table 2, and the physical property data of the surface-modified SAP resin are shown in Table 3.

[0035] Example 4

[0036] The surface modification crosslinking agent of this embodiment includes the following raw materials in parts by weight: 27.3 parts of propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 10.2 parts of liquid silicon with a concentration of 30wt%, and 60.4 parts of water; wherein the liquid silicon used is an amino-modified nano-SiO2 dispersion, which is an aqueous dispersion, wherein the particle size of the nano-SiO2 is less than 50nm and the specific surface area is at least 20m 2 / g;

[0037] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin are shown in Table 3.

[0038] Example 5

[0039] The surface modification crosslinking agent of this embodiment includes the following raw materials in parts by weight: 27.3 parts of propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 20.4 parts of liquid silicon with a concentration of 30wt%, and 50.2 parts of water; wherein the liquid silicon used is an amino-modified nano-SiO2 dispersion, which is an aqueous dispersion, wherein the particle size of the nano-SiO2 is less than 50nm and the specific surface area is at least 20m 2 / g;

[0040] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin are shown in Table 3.

[0041] Comparative Example 1

[0042] The surface modified cross-linking agent of this comparative example includes the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether and 68.2 parts of water;

[0043] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin in this comparative example is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin in this comparative example are shown in Table 3.

[0044] Comparative Example 2

[0045] The surface modified cross-linking agent of this comparative example includes the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 1.77 parts of fumed silica, and 68.2 parts of water;

[0046] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin in this comparative example is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin in this comparative example are shown in Table 3.

[0047] Comparative Example 3

[0048] The surface modified cross-linking agent of this comparative example includes the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 31 parts of liquid silicon with a concentration of 30wt%, and 46.5 parts of water;

[0049] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin in this comparative example is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin in this comparative example are shown in Table 3.

[0050] Comparative Example 4

[0051] The surface modified cross-linking agent of this comparative example includes the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 1.77 parts of hydrotalcite, and 68.2 parts of water;

[0052] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin in this comparative example is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin in this comparative example are shown in Table 3.

[0053] Comparative Example 5

[0054] The surface modified cross-linking agent of this comparative example includes the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 5 parts of sodium alum, and 63.2 parts of water;

[0055] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin in this comparative example is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin in this comparative example are shown in Table 3.

[0056] Comparative Example 6

[0057] The surface modified cross-linking agent of this comparative example includes the following raw materials in parts by weight: 27.3 parts of 1,2-propylene glycol, 4.5 parts of ethylene glycol diglycidyl ether, 0.48 parts of Tween 60, and 67.7 parts of water;

[0058] The surface modification method is the same as that in Example 2. The particle size of the surface-modified SAP resin in this comparative example is analyzed by screening and the particle size distribution is calculated. The particle size data is shown in Table 2. The physical property data of the surface-modified SAP resin in this comparative example are shown in Table 3.

[0059] The surface modification crosslinking agent formulations of the above embodiments and comparative examples are shown in Table 1.

[0060] Table 1 Surface modification crosslinking agent formulations of the embodiments and comparative examples (parts by weight)

[0061]

[0062]

[0063] Table 2 Particle size distribution of SAP after crosslinking agent surface modification in the examples and comparative examples

[0064]

[0065] In the following analysis, particles larger than 850 μm are referred to as large particles, particles between 600 and 850 μm are referred to as medium particles, particles smaller than 600 μm are referred to as small particles, and particles smaller than 150 μm are referred to as microparticles. As shown in Table 2, after crushing and screening, the SAP base resin does not contain large particles and has very little medium particles, and most of them are small particles. After all surface modifications, a small amount of large particles and a large number of medium particles are produced. When the liquid silicon used in the present invention accounts for 5-25% of the crosslinking agent, the particles with a particle size of less than 600μm after surface modification account for more than 65%, and the particles with a particle size of more than 850μm account for less than 4%; when the liquid silicon used in the crosslinking agent accounts for 5-10%, the particles with a particle size of less than 600μm after surface modification account for more than 75%, and the particles with a particle size of more than 850μm account for less than 2.5%; when the liquid silicon used in the crosslinking agent accounts for 5-6%, the particles with a particle size of less than 600μm after surface modification account for more than 80%, and the particles with a particle size of more than 850μm account for less than 2.2%. The liquid silicon used in the present invention accounts for 5-25% (preferably between 5-10%, more preferably between 5-6%) in the crosslinking agent, which has good anti-particle aggregation performance for SAP resin particles to aggregate into medium particles and large particles. In comparative example 3, as the liquid silicon content increases to 28%, the proportion of large particles reaches 4%, the proportion of medium particles reaches 33.85%, and the anti-aggregation property decreases. Comparative example 2 using the corresponding amount of gas silicon is slightly worse than Example 2 of the present invention. The proportion of large particles in Example 2 is reduced by 0.16%, which is considered to be equivalent to Example 2. However, the proportion of medium particles in Example 2 is 7.35% more, and the proportion of small particles in Example 2 is 7.19% less. The overall effect of controlling particle size distribution is slightly worse than that of the present invention using liquid silicon. The effects of controlling particle size distribution in comparative examples 4-6 are also not ideal.

[0066] Table 3 Physical properties of SAP after crosslinking agent surface modification in Examples and Comparative Examples

[0067]

[0068]

[0069] As shown in Table 3, compared with the conventional surface modification crosslinking agent formula without additives and the surface modification crosslinking agent formula containing additives (LDH, sodium alum, Tween 60), the surface modification crosslinking agent formula containing liquid silicon in the present invention has obvious advantages in the performance of SAP physical properties, and can significantly improve the liquid permeability and gel bed permeability (GBP) while maintaining the centrifugal liquid retention rate (CRC) and the absorption rate under load (0.7psiAAP). The most inadequate aspect of the surface modification crosslinking agent formula containing fumed silica in the performance of SAP physical properties is that it will significantly reduce the absorption rate under load (0.7psiAAP).

[0070] Summary: From the combination of Table 2 and Table 3, the optimal formula is the formula in Example 2 and Example 3. After surface modification, the particles with a particle size less than 600 μm account for more than 80%, and the particles with a particle size greater than 850 μm account for less than 2.2%. The liquid permeability of the modified SAP is greatly improved, and other physical properties such as centrifugal water retention rate and pressurized absorption rate are not reduced.

[0071] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A particle size control surface modification method for a polymer water-absorbing resin, characterized in that: The method comprises the following steps: preparing a surface modified cross-linking agent, mixing the cross-linking agent with a SAP base resin in an atomized form, and performing a heat treatment at 130° C. for 40 minutes to obtain a surface modified SAP resin, wherein after the surface modification, particles with a particle size of less than 600 μm account for more than 65% and particles with a particle size of more than 850 μm account for less than 4%; The surface modification cross-linking agent comprises the following raw materials in parts by weight: 25-28% of a hydrophilic polyol above C3, 3-5% of an ether compound that reacts with a carboxyl group to form a covalent bond, 5-10% of liquid silicon, and the balance is water; The liquid silicon is a dispersion containing 20-50% by mass concentration of nano-silicon dioxide, wherein the particle size of the nano-silicon dioxide is less than 50 nm and the specific surface area is at least 20 m 2 / g; the nano-silica is amino-modified nano-SiO2; The hydrophilic polyol with C3 or above is propylene glycol; and the ether compound that reacts with the carboxyl group to form a covalent bond is ethylene glycol diglycidyl ether.

2. The particle size control surface modification method of a polymer water-absorbing resin according to claim 1, characterized in that: The surface modification cross-linking agent is used in an amount of 1-5% by weight of the SAP base resin.

Citation Information

Patent Citations

  • Water absorbent resin particles and production method therefor

    CN111868145A